Development of large-scale gastruloid array to identify aberrant developmental phenotypes - Ian Jan; Andrew Cearlock; Min Yang; Nancy L. Allbritton (APL Bioengineering)
Adherent two-dimensional human gastruloids have provided insights into early human embryogenesis. Even though the model system is highly reproducible, no available automated technology can screen and sort large numbers of these near-millimeter-sized complex structures for large-scale assays. Here, we developed a microraft array-based technology to perform image-based assays of large numbers of fixed or living gastruloids and sort individual gastruloids for downstream assays, such as gene expression analysis. Arrays of 529 indexed magnetic microrafts each (789 µm side length) possessing flat surfaces were photopatterned with a central circular region (500 µm diameter) of extracellular matrix with an accuracy of 93 ± 1% to form a single gastruloid on each raft. An image analysis pipeline extracted features from transmitted light and fluorescence images of the gastruloids. The large microrafts were released and collected by an automated sorting system with efficiencies of 98 ± 4% and 99 ± 2%, respectively. The microraft array platform was used to assay individual euploid and aneuploid (possessing abnormal numbers of chromosomes) gastruloids with clear phenotypic differences. Aneuploid gastruloids displayed significantly less DNA/area than euploid gastruloids. However, even gastruloids with the same condition displayed significant heterogeneity. Both noggin (NOG) and keratin 7 (KRT7), two genes involved in spatial patterning within gastruloids, were upregulated in aneuploid relative to that in the euploid gastruloids. Moreover, relative NOG and KRT7 expressions were negatively correlated with DNA/area. The microraft arrays will empower novel screens of single gastruloids for a better understanding of key mechanisms underlying phenotypic differences between gastruloids.